Maria Sibylla Merian (1647-1717) e seu metamorphosis insectorum surinamensium: um percurso entre arte e história natural - Araújo, Luma Cabrera de (2022)
Maria Sibylla Merian’s work has such a rich amount of information that it is possible to study it from different perspectives. In both Der Raupen and Metamorphosis insectorum Surinamensium she focuses on the metamorphoses of insects, especially moths and butterflies. Nonetheless, Maria Merian merged her artistic skills with the observational knowledge she was acquiring as her research progressed. She created images that summarized all the phases of transformation allied to the plants that served as nourishment for these species. The effect this has is, at the same time, simple and admirable: the mere visualization of her images provided much of the story she wanted to tell. Her texts supplied the rest: an insect’s preferred food type, typical caterpillar behaviour, duration of the chrysalis period, morphological characteristics, and so on. From this perspective, the present dissertation aims to analyze, especially, her work on Suriname, which followed the same line as her works on European insects, acquiring even more notoriety. By presenting themes related to the relationship between human beings and nature, she left for posterity precious information about how indigenous people, black enslaved people, and European settlers dealt with the resources available in the colony. This gives rise to descriptions of the uses of plants and animals for food, healing strategies, certain customs linked to the daily life of the region, and the economic dimension of Dutch colonization in Suriname, at last, all these aspects combined with the precious watercolours typical of Maria Merian